Detection and Genetic Characterization of Seoul Virus in Liver Tissue Samples From Rattus norvegicus and Rattus tanezumi in Urban Areas of Southern China - He, Wenqiao; Fu, Jiaqi; Wen, Yuqi; Cheng, Mingji; Mo, Yun; Chen, Qing (Frontiers in Veterinary Science, 2021)
Rodents are important hosts of hantaviruses, and lungs and kidneys are known to be the preferred organs of these viruses. Recently, hantaviruses were detected in liver samples from wild rodents in Hungary and the United States, and feeder rats in the Netherlands. However, few studies have detected hantaviruses in the liver of rats from China. In this study, hantaviruses were investigated in liver samples from R. norvegicus and R. tanezumi trapped in urban areas of southern China. A total of 461 R. norvegicus and 64 R. tanezumi were trapped. Using a pan-hantavirus PCR method, hantaviruses were detected in liver, lung, and serum samples from these animals. About 7.43% of liver samples were positive for Seoul virus (SEOV). The detection rate of SEOV in liver samples from R. norvegicus (8.24%) was higher than that from R. tanezumi (1.56%), suggesting the predominant role of R. norvegicus in the transmission of SEOV in urban areas of China. Three R. norvegicus had SEOV RNA in their liver samples but not in their lung samples, suggesting that the liver might be one of the targeted organs of SEOV. The first full SEOV protein-coding sequences (CDS) of the S and M segments, and partial CDS of the L segment from R. tanezumi were amplified. Several full and partial CDS of the S, M, and L segments from R. norvegicus were also obtained. The SEOV sequences obtained from different animals were highly similar, suggesting the cross-species transmission potential of SEOV between R. norvegicus and R. tanezumi.